PERUBAHAN PAJAK TERKAIT TARIF PROGRESIF PADA PENGHASILAN (PPH) PERORANGAN DI INDONESIA DITINJAU DARI AZAS KEADILAN - Riady, Johannes Agustinus; Ratnawati, Elfrida (Ensiklopedia of Journal, 2024)
The government officially issued the Harmonization of Tax Regulation Act (UU HPP) regulated in Law no. 7 of 2021, in the year 2021. This was established to streamline tax regulations by consolidating various provisions resulting from amendments from several previous tax laws into a single law. One of the objectives of this law is to provide different treatments to taxpayers based on their different capabilities to pay taxes. In accordance with the principle of vertical equity in tax collection, this aligns with the principle of unfairness to the unjust. The problem formulation taken is: Does the issuance of Law No. 7 of 2021 on the Harmonization of Tax Regulations concerning personal income tax (PPh) comply with the Principle of justice? The research method used in this issue is the Normative research method, which will be analyzed descriptively. Studies indicate that the progressive rate changes in the HPP Law are intended to increase the progressive tax rates on individual income tax by adding a new top layer with a higher income range than the range in the previous rules. The purpose of these progressive rate changes is to enhance the principle of fairness and concern for low-income taxpayer groups. Thus, at a glance, one of the principles of tax fairness, namely the Ability to Pay Principle, where taxes are levied based on the taxpayer's ability to pay, has been fulfilled.Keywords: Personal Tax, Progressive Rate, Principle of Justice